Fuel sharing in expeditionary operations. (January 2019) - Doerr, Kenneth H.; Ferrer, Geraldo
Highlights: Presents post-supply-chain logistics decision necessary in expeditions. Models fuel sharing between dispersed expeditionary units. Models mission risk as an objective. Extended numerical example of historic interest. Abstract: Expeditionary units operate beyond the normal supply chain. We examine a situation in which expeditionary units are dispersed and moving forward to achieve some mission objective. The logistics decision must be made: should resources (fuel) be shared between those expeditionary units. Our criterion is mission risk, or the probability the expeditionary mission succeeds. Mission risk is modeled as a function of both logistics risk and operational risk. We present a model of fuel sharing which incorporates this balance of risks and we demonstrate the effectiveness of fuel sharing in an extended numerical example, based on historical data from the Ardennes campaign in WWII.